Identification of Resistant Sources against Sheath Blight of Rice Caused by Rhizoctonia solani Kuhn - Arpitha, H. B.; Kumar, N. Kiran; Kumar, L. Vijay; Ashoka, K. R.; Pankaja, N. S.; Mallikarjuna, N. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during kharif (July-November) seasons of 2023 and 2024 at V.C. Farm, Mandya, Karnataka, India to identify the resistant genotypes for sheath blight of rice. 240 (Two hundred and forty) popular landraces were screened against sheath blight disease under field condition by artificial inoculation method. The inoculum of R. solani was prepared by mass multiplication on sorghum grains and applied at the tillering stage, thirty-days after transplanting. The sorghum grains colonized by the fungus were used for field inoculations on thirty-days old plants. The disease scoring was done by the standard evaluation system (SES) as per IRRI (2013). The mean percent disease index (PDI) of both the seasons ranged from 5.43 to 61.11% and the AUDPC exhibited the values ranging from 176.28–334.41. Based on mean PDI and AUDPC values, rice genotypes were categorized into 5 groups i.e., resistant, moderately resistant, moderately susceptible, susceptible and highly susceptible. None among the 240 landraces screened over two seasons, exhibited an immune response with a score of 0. However, seven genotypes showed a resistant reaction with the score of 1. Seventy-two genotypes which exhibited a score of 5 were categorized as moderately susceptible while, seventy genotypes with the score of 7 were classified as susceptible and thirty-one genotypes were identified as highly susceptible, scoring 9.